Protective Effects of Sida Veronicaefolia against Paracetamol Induce Hepatotoxicity in Experimental Animals - Jain, Vidhi; Singh Saluja, Manmeet (Journal of Biomedical and Pharmaceutical Research, 2022)
In the current research, rats will be given paracetamol (hepatotoxic), and the hydoethanol (HEESV) extract of the leaves of Sida veronicaefolia will be tested to see how well it protects the rats' livers from damage caused by the paracetamol. Liver function tests and serum profiles were used to provide an estimate of the hepatoprotective effects of HEESV at a dose of 500 mg/kg. According to the findings, the extracts of the chosen plant not only provide a strong hepatoprotective impact by lowering blood levels of serum transaminases (SGPT and SGOT), alkaline phosphate, and total bilirubin, but they also considerably enhance the levels of total protein. The effects of HEESV were quite similar to those of the standard medication silymarin.